Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Taquia Valdivia, Manuel Alonso (2018)
The following report seeks to support the investment decision of the corporation, with focus on the internal and external factors that ensure the success of the Japanese firm under the leadership of its CEO, Tadashi Yanai. The leadership is not their only competitive advantage, as the company maintains a solid organizational structure with sufficient bargaining power to ensure the best products with high quality standards and fair prices. Additionally, external factors present positive trends that outstand the negative ones. Also, an analysis of the value chain, competitive advantages and the industry was carried out in the present case, concluding that the country is an attractive market for the investment to be made. With the implementation of the proposed strategies, the achievement of promising strategic objectives will be possible, ensuring the success of the UNIQLO chain (main company of Fast Retalling corporation) in our country.